2021
DOI: 10.3389/fped.2021.658094
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Home Parenting Environment on Cognitive and Psychomotor Development in Children Under 5 Years Old: A Meta-Analysis

Abstract: This study aims to evaluate the relationship between home parenting environment and the cognitive and psychomotor development in children under 5 years old by using meta-analysis. A systematic search of the Chinese and English databases including Pubmed, Embase, the Cochrane Library, CNKI, Weipu, Wanfang, and CBMdisc databases from January 1, 1990, to July 31, 2021, was performed. Articles concerning the relationship between home parenting environment and the cognitive and psychomotor development in children u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 43 publications
1
15
0
2
Order By: Relevance
“…The overall effect was compounded by mothers’ PA experience, income, mother age, and education. Our findings underscore the conclusion of an extensive literature review by Yang and colleagues [ 48 ] noting that there is a positive correlation between the home parenting environment and the psychomotor development of young children. Furthermore, improving the home environment is a key factor in promoting early child development.…”
Section: Discussionsupporting
confidence: 85%
“…The overall effect was compounded by mothers’ PA experience, income, mother age, and education. Our findings underscore the conclusion of an extensive literature review by Yang and colleagues [ 48 ] noting that there is a positive correlation between the home parenting environment and the psychomotor development of young children. Furthermore, improving the home environment is a key factor in promoting early child development.…”
Section: Discussionsupporting
confidence: 85%
“…First, in the theory of cognitive dissonance ( 14 ), cognitive dissonance is caused by two or more inconsistent notions or by the discrepancy between individuals' behaviors and values, which was an important risk factor for mental health ( 15 , 16 ). Considering the importance of parental parenting style on children's and adolescents' cognitive development ( 17 , 18 ), we have enough reasons to believe the impact of parental parenting style disparities on children's and adolescents' mental health. Second, many previous studies had identified the strong effect of parental characteristics on their children's mental health ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…and/or SES vs. diet generally contribute more to the ECC-psychomotor deficiency axis than onto traditional ECC activity may enable bridging the biologic vs. social interactions on the existing risks for ECC, thereby signifying the development of psychomotor deficiency over time [ 21 ]. For example, it has recently been shown that there were good correlations between: (i) a home-parenting environment and cognitive and psychomotor development for children under five years old, and (ii) preschool children diagnosed with attention deficit hyperactivity disorder (ADHD) and the parents’ perception of difficulties in several dimensions of development and global learning difficulties, such as expressive language, comprehension, and fine motor skills, as well as in emotions, concentration, behavior, and relationships [ 47 , 48 ]. Similarly, comparable findings may be extended to younger toddlers with developmental delays, where such delays can also affect the children’ physical, cognitive, communication/speech, social, emotional, or behavioral skills [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conceivably, such events may emerge at some critical stages, likely throughout childhood growth via language communications and some peer social/psycho-mental engagements [ 13 ]. Scientifically, we will need to investigate and further implement the differential roles and/or contributions of specific SES vs. dietary categorical measures regarding the hypothesized theme proposed [ 26 , 27 , 28 , 29 , 32 , 34 , 35 , 36 , 48 ], consisting of a direct neurophysiologic path and/or an indirect one external to the neurologic circus [ 13 , 18 , 21 ].…”
Section: Discussionmentioning
confidence: 99%